Chitosan Oligosaccharide Production Potential of Mitsuaria sp. C4 and Its Whole-Genome Sequencing - Chen, Duo; Chen, Congcong; Zheng, Xuehai; Chen, Jiannan; He, Wenjin; Lin, Chentao; Chen, Huibin; Chen, Youqiang; Xue, Ting (Frontiers in Microbiology, 2021)
Chitooligosaccharide is a kind of functional food, which is the degradation product of chitosan catalyzed by endo-chitosanase (COSE) enzyme. A COSE with a molecular weight of 34 kDa was purified and characterized from a newly isolated Mitsuaria sp. C4 (C4), and a 38.46% recovery rate and 4.79-fold purification were achieved. The purified C4 COSE exhibited optimum activity at 40 ℃ and pH 7.2 and was significantly inhibited in the presence of Cu2+ and Fe3+. The Km and Vmin of the COSE towards chitosan (COS) were 2.449 g/L and 0.042 g/min/L, respectively. The highest COSE activity reached to 8.344 U/mL after optimizing, which represented a 1.34-fold of increase. Additionally, chitooligosaccharide obtained by COSE hydrolysis of COS were verified by using TLC and HPLC analysis. Whole-genome sequencing demonstrated that the C4 strain contains 211 carbohydrate enzymes, our purified COSE belonging to GHs-46 involved in carbohydrate degradation. Phylogenetic analysis showed that the novel COSE obtained from C4 strain was clustered into the DP=2-3 group, which can perform catalysis in a similar manner to produce (GlcN)2 and (GlcN)3. This work indicates that the C4 strain could be a good resource for enhancing carbohydrate degradation and might represent a useful tool for chitooligosaccharide production in functional food industry.